Peningkatan Kebermaknaan dan Hasil Belajar Siswa melalui Desain Pembelajaran Tematik Terpadu Berbasis Projek di Sekolah Dasar - Saadah, Mutiatus; Mawardi, Mawardi (JARTIKA: Jurnal Riset Teknologi dan Inovasi Pendidikan, 2019)
This research is motivated by the problems of thematic learning in SD Negeri Gendongan 02 which is less meaningful. This problems lead to low learning outcomes. Pre-cycle results show that 24 students out of 38 students met the KKM (School Minimum Requirement Score). 14 students have not reached the KKM. To overcome this problem, researchers chose an alternative integrated thematic learning design based on project to improve student meaningfulness and learning outcomes. This type of research is classroom action research using the Stringer model. Research subjects involved 38 students in grade 5. Data collection using questionnaires, written tests, documentation and observation sheets. Data analysis techniques uses descriptive comparative. The results showed that the meaningful learning cycle 1 was 92.11% increasing to 97.73%. Indonesian language learning outcomes in cycle 1 is 84.21% increasing to 86.84%. Learning outcomes of science studies in cycle 1 is 65.79% and increased to 84.21%. Based on the results of these research, alternative integrated thematic learning designs based on projects can improve the meaningfulness and learning outcomes of grade 5.